Quality of life among patients with brain pathology in a Malaysian hospital - Das, Priscilla; Naing, Nyi Nyi; Wan Abdul Jamil, Wan Arfah Nadiah; Khin, Ohnmar Naing @ Noor Jan; Kueh, Yee Cheng; Rasalingam, Kantha (Universiti Putra Malaysia Press, 2019)
The objective of this study was to determine the prevalence of symptoms and problems in Malaysian brain pathology patients. A total of 100 respondents in Kuala Lumpur Hospital were included in this cross-sectional study. The study utilized European Organization for Research and Treatment of Cancer Quality Of Life questionnaire (EORTC QLQ-C30). Patient with a "symptom/problem" having the minimum response of "a little". A response of "quite a bit" was defined as having a "severe symptom/problem". The two most prevalent "symptoms/problems" among the neurological disorder patients were fatigue (65%; severe: 28%) and reduced cognitive functioning (64%; severe: 25%). The mean number of "symptoms/problems" ranged from 4.63 (meningioma) to 6.80 (cerebellar edema) while the mean number of "severe symptoms/problems" ranged from 1.39 (astrocytic glioma) to 2.8 (cerebellar edema). Therefore special attention should be given to these patients in order to improve the overall quality of life of the patients.